On the hydrological difference between catchments above and below the intermittent‐persistent snow transition - Harrison, Hannah N.; Hammond, John C.; Kampf, Stephanie; Kiewiet, Leonie (Hydrological processes, 2021)
Because of the importance of snow for river discharge in mountain regions, hydrological research often focuses on seasonally snow‐covered zones. However, in many basins the majority of the land surface area is intermittently snow‐covered. Discharge monitoring in these areas is less common, so their contributions to downstream rivers remain largely unknown. We evaluated hydrological differences between three intermittently snow‐covered (mean annual Jan 1–Jul 3 snow persistence <60%) and two seasonally snow‐covered headwater catchments in the Colorado Front Range. We compared water balance variables to evaluate how and why discharge differs between the snow zones and estimated the relative contributions from each snow zone to regional river discharge. We focused on water years 2016–2019 and used a combination of in situ sensors and regional climate datasets. Annual discharge from the intermittent snow zone was low for all three catchments (10–77 mm), despite covering a wide range in annual snow persistence (25%–64%), whereas annual discharge from the seasonal snow zone was up to 73 times higher. Soil moisture in the seasonal snow zone was above field capacity for longer periods of time than in the intermittent snow zone, and the intermittent snow zone was uniquely subject to soil freezing (up to 102 days per year). For most of the year, potential evapotranspiration exceeded rainfall and snowmelt inputs in the intermittent snow zone, but was lower than rainfall and snowmelt inputs in the seasonal snow zone. This is likely a primary driver of the differences in soil moisture and discharge for catchments with a seasonal versus intermittent snow cover. Despite the large difference in discharge between these two snow zones, the intermittent snow zone contributed about a quarter of the discharge in the regional river, highlighting the importance of studying discharge generation across all elevations. Mountain regions have steep climate gradients that substantially affect streamflow generation. To understand streamflow in mountainous catchments, both the seasonally and the intermittently snow‐covered areas within these catchments should be considered. By comparing water fluxes in seasonally and intermittently snow‐covered catchments and estimating their contributions to the regional watershed, we determined that discharge is low across the intermittent snow zone, but provides roughly one fourth of the regional flow. This highlights the importance of studying discharge generation across elevations.